Regulation of Brown Adipose Tissue Activity by Interoceptive CNS Pathways: The interaction between Brain and Periphery - Muzik, Otto; Diwadkar, Vaibhav A. (Frontiers in Neuroscience, 2017)
For the defense of body temperature, efferent signals from central thermoregulatory networks regulate metabolism in specific thermogenic tissues. Among them, nonshivering thermogenesis in brown adipose tissue (BAT) has been implicated as a heat source for the defense of body temperature in cold environments. To maintain thermal homeostasis, efferent signals from central thermoregulatory networks regulate metabolism in specific thermogenic tissues. One of these mechanisms involves nonshivering thermogenesis in brown adipose tissue (BAT), which has been implicated as a heat source for the defense of body temperature in cold environments. The objective of our study was to assess the interaction between CNS thermoregulatory pathways and sympathetic innervation in BAT during a cold exposure paradigm. Our results show that an innocuous whole-body cooling paradigm induces significant differences in fMRI BOLD signal at the location of the right anterior insula and the red nucleus/substantia nigra region, between lean subjects with high levels of sympathetic innervation in supraclavicular BAT (BAT+ group), and subjects with low levels of sympathetic innervation (BAT- group). Specifically, results indicate significantly larger fMRI BOLD signal changes between periods of cooling and warming of the skin in the BAT+ (as compared to BAT-) group at the location of the right anterior insula. In contrast, the BAT+ group showed significantly smaller fMRI BOLD signal changes in the midbrain between periods of skin cooling and warming. Our findings are consistent with a hierarchical thermoregulatory control system that involves the initiation of inhibitory signals from the right anterior insula towards midbrain areas that normally exert tonic inhibition on the medullary raphe, from where BAT is directly innervated. Our data suggests that exposure to cold elicits differential neuronal activity in interoceptive regulatory centers of subjects with high and low level of sympathetic innervation. As a result, the variability of cold-activated BAT mass observed in humans might be, in part, yoked to different sensitivities of interoceptive cortical brain areas to skin temperature changes.